2017
DOI: 10.1093/aob/mcw262
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analyses of the inheritance and expressivity of autonomous endosperm formation in Hieracium with different modes of embryo sac and seed formation

Abstract: Background and Aims Apomixis, or asexual seed formation, in polyploid Hieracium subgenus Pilosella species results in clonal progeny with a maternal genotype. An aposporous embryo sac forms mitotically from a somatic cell, without prior meiosis, while embryo and endosperm formation is fertilization independent (autonomous). The latter two developmental components are tightly linked in Hieracium. Recently, two plants, AutE196 and AutE24, were identified from two different crosses. Both form embryo sacs via the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…However, further investigation of the LOP locus uncovered rare recombination events between the parthenogenesis phenotype and the autonomous endosperm phenotype, consistent with two tightly linked genes ( LOP and Autonomous Endosperm, abbreviated as AutE ). Unexpectedly, the genetic fine mapping of AutE in more crosses showed that this locus was on a different linkage group from the LOP locus, with a low penetrance (18%) and no additive effect [ 15 ], suggesting that the AutE phenotype in Hieracium is controlled by a more complex genetic mechanism than LOA or LOP .…”
Section: Introductionmentioning
confidence: 99%
“…However, further investigation of the LOP locus uncovered rare recombination events between the parthenogenesis phenotype and the autonomous endosperm phenotype, consistent with two tightly linked genes ( LOP and Autonomous Endosperm, abbreviated as AutE ). Unexpectedly, the genetic fine mapping of AutE in more crosses showed that this locus was on a different linkage group from the LOP locus, with a low penetrance (18%) and no additive effect [ 15 ], suggesting that the AutE phenotype in Hieracium is controlled by a more complex genetic mechanism than LOA or LOP .…”
Section: Introductionmentioning
confidence: 99%
“…In R35 the dominant LOSS OF PARTHENOGENESIS ( LOP ; Figure 1 B) locus controls fertilization-independent embryogenesis and endosperm formation [ 11 , 12 ]. An additional locus has been identified in D36 termed AutE which enables fertilization-independent endosperm formation [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Engineering the autonomous formation of the endosperm without fertilization to obtain a complete asexual system may be ideal from a biotechnological perspective. From a biological viewpoint, despite studies showing that a single dominant locus is able to induce the autonomous endosperm phenotype in apomictic Hieracium [144], inducing autonomous endosperm in sexuals might be hard due to the molecular complexity of its development. Autonomous endosperm development differs between dicots and monocots, and the dynamics underlying this complex process rely on genome balance, epigenetic gene regulation, and parent-of-origin effects founded upon the contribution of the male gamete [145].…”
Section: Mimicking Gametophytic Apomixismentioning
confidence: 99%
“…Autonomous endosperm development differs between dicots and monocots, and the dynamics underlying this complex process rely on genome balance, epigenetic gene regulation, and parent-of-origin effects founded upon the contribution of the male gamete [145]. In addition, still unknown genetic modifier elements, protein interactions, and regulatory pathways underlying embryo-endosperm developments add to the complexity [101,146,147] and restrain autonomous endosperm expressivity [144]. Regardless of mutations in fertilization independent endosperm (FIE) and other Polycomb group genes leading to autonomous endosperm development in Arabidopsis [148], orthologs reported in both rice (OsFIE1 and OsFIE2) and maize (ZmFIE1 and ZmFIE2; [149]) produce distinct phenotypes.…”
Section: Mimicking Gametophytic Apomixismentioning
confidence: 99%